Faktor-faktor yang Berhubungan dengan Kepemilikan Anjing di Kabupaten Karangasem, Provinsi Bali - Kepeng, I Nengah; Puja, I K.; Dharmawan, N.S. (Veterinary Science and Medicine Journal; Vol 2 No 1 (2014), 2014)
Bali province has been declared as rabies endemic area. Bali government has already implemented several efforts to control rabies, but it does not have any significant impact to make Bali free from the disease. This condition is not caused by limited resources only, but also by factors of socio-demographic dog’s ownership. This observational study using cross sectional design has been done to determine the public's knowledge and dog’s ownership related factors in Karangasem Regency. Nine villages were selected based on the positive rabies cases, which was formerly confirmed by laboratory tests. The Villages were divided into three category based on the socio-economic and culture, namely urban, sub urban and rural area. Data were analyzed descriptively and by multivariate logistic regression analysis. The results showed that from the 408 households, 252 respondents (61.8%) reported having the dogs. The percentage of dog ownership in urban, sub urban and rural is 17.6%, 9.8% and 34.3% respectively. It can be suggested that the rural area should be a priority in controlling rabies in Karangasem Regency.
Keywords: rabies; dog ownership; Karangasem Regency